Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional Dan Penyebaran Kepemilikan Terhadap Struktur Modal Perusahaan - Anang Subardjo (BIP's JURNAL BISNIS PERSPEKTIF, 2011)
The purpose of this research is to test the inJluence of managerial ownership, institutional ownership, and shareholder dispersion on capital structure companies. Data collection is done by using pooling method. 39 firms listed in Jakarta Stock Exchange for period 2008-2009 used as samples. This research provides evidence that first, managerial ownership has negative and significant effect to capital structure (debt ratio)- Second, institutional ownership has negative and significant effect to capital structure. Third, shareholder dispersion has negative but not significantly effect to capital structure(debt to ratio).